Analysis of the characteristics of patients admitted to Internal Medicine wards for exacerbation of chronic obstructive pulmonary disease, and discharge phase optimization. The SDO-ARCA Project of the Scientific Society FADOI - Marco Candela; Claudio Norbiato; Mauro Campanini; Antonio Luca Brucato; Salvatore Di Simone; Dario Manfellotto; Francesco Dentali; Antonio Sacchetta; Antonella Valerio; Andrea Fontanella (Italian Journal of Medicine, 2020)
The purpose of this study was to have a nationwide snapshot of the characteristics of patients hospitalized in Internal Medicine Units (IMUs) for exacerbation of chronic obstructive pulmonary disease (COPD), and to assess applicability and contents of a specific Hospital Discharge Form for the patient with exacerbation of COPD discharged from IMUs. This was a prospective study in 44 IMUs in Italy, enrolling patients hospitalized with a diagnosis of COPD exacerbation. Information concerning clinical characteristics of patients, and treatment for COPD at discharge was collected. Specific documents for monitoring of clinical conditions and adherence to therapies as well as a form including individual indications for clinical controls, instrumental tests, etc. were provided upon discharge. Four hundred and seventy-two patients were enrolled (68% male). According to GOLD classification 2015, patients with classes A to D were 12%, 27%, 31%, and 30%, respectively. Triple therapy was prescribed in 14% of GOLD A and 51% of GOLD D patients. Around 10% of patients for each GOLD class received no specific therapy. The vast majority of patients (85%) received instructions on the correct use of inhalers, and in most cases (85%), the quality of counseling was considered optimal/adequate. Indication for performing chest X-ray, spirometry, or blood gas analysis following discharge was addressed to 29%, 59% and 52.1% of patients, respectively. The follow-up sheet for COPD used in our study was shown as applicable. This highlighted the need for greater awareness and more standardized procedures within IMUs in the post-discharge phase.